Addition and subtraction word problem tasks in reform‐based textbooks. (23rd April 2021) - Ma, Xiaojun; Bofferding, Laura; Xin, Yan Ping
Abstract: One of the factors associated with the less than positive mathematics performance of American students could be poorly designed textbooks that fail to facilitate the development of critical mathematical ideas. This study examined two reform‐based textbooks (Go math! and Investigations) in reference to essential, mathematical big ideas emphasized in the Essential Understanding Series (EU) presented by NCTM against the backdrop of mathematics education reform. In particular, we analyzed the features of the lessons for teaching addition and subtraction word problem solving. In some aspects, the results indicated that in terms of teaching problem comprehension and algebra readiness, the two textbook series showed improvement compared to formerly used textbooks. However, both textbook series may fall short of reflecting some important EU big ideas (e.g., teaching the underlying structure and part‐part‐whole relation of addition and subtraction word problems; providing students with chances to deal with exhaustive problem types and situations). In particular, our findings highlight the need for teaching word problem solving through building abstract level conceptual understanding. Implications for future textbook developing and limits are discussed.